Unravelling the routines in new product development portfolio management. - Tjaturpriono, Hendro Adiarso (Cranfield University, 2017)
Product innovation is a key driver of growth. One of the biggest challenges facing an organisation in managing product innovation is determining the most promising new product development (NPD) projects from the many ideas generated. This selection process is known as NPD portfolio management, which is a strategic decision-making process. Despite its significance in terms of management practice, portfolio management is still not well understood, either by practitioners or academics. For example, much of what has been written focuses mainly on individual project selection rather than managing the entire process; at the same time, it is unclear how to manage the link between the portfolio decisions and business strategy. A systematic review was carried out of the different streams of literature addressing portfolio management, strategic decision-making, the strategy process and organisational routines. The review showed that the theoretical perspective of organisational routines has not been adopted in previous studies of portfolio decision-making. This is a significant omission, as organisational routines constitute an important theoretical perspective, able to uncover not only the formal but also the informal ways in which portfolio decisions are made. Based on the gaps identified in the systematic literature review, three research questions were adopted: 1) How is new product development portfolio management conducted?; 2) What organisational routines can be identified in the new product development portfolio management in companies?; 3) Is the company’s espoused business strategy considered in the new product development portfolio management (as evidenced in routines)? These questions were addressed by case study research conducted in four manufacturing firms based in Indonesia, from the cosmetics, food, consumer and automotive sectors. The study focused on how the firms conduct portfolio management. It used multiple sources of data: semi-structured interviews with directors and managers; inspection of portfolio management process documentation; attendance at a product development meeting; and a simulation exercise which involved observing the approach managers took in selecting a product portfolio. The findings show that across the four companies, a total of 12 routines could be identified that are connected to portfolio management. These routines were termed a ‘palette’ of routines connected to portfolio management, from which the routines relevant to a particular organisation can be selected. Further analysis refined these 12 routines into eight key routines. Five of the eight routines were identified to be ‘core’ (Market and Industry Analysis, Concept Selection and Development, Build Business Case, Portfolio Management Review and Product Development), as all four case companies used them. Two additional routines were found to be ‘essential’ (Business Planning and Project Prioritisation); one is ‘optional’ (New Product Research). While in the literature, portfolio management is centred solely upon making decisions about which projects will be selected, the palette of routines unveils the entire process of portfolio management as more wide-reaching and complex. Surprisingly, the study also discovered that a linkage between the routines and business strategy – something that the literature claims is missing – existed in all four case companies (albeit in largely informal routines rather than as part of formal processes). From a practical point of view, the study generated a generic framework for portfolio management. This enables a company to build its portfolio management on the seven routines that were identified as “core” and “essential”, supplemented with an extra routine if required, depending on the business strategy. This framework can help managers to design an effective NPD portfolio management process. Overall, portfolio management is an under-researched area, despite its strategic importance. This study has demonstrated that portfolio management is wider-reaching that previously thought; it is dependent on both formal processes but also undocumented routines, and it links much more closely to company strategy than previously thought. However, more research is needed.